Characterization of foreign patients confirmed with the COVID - 19 in Santiago de Cuba - Sirce Rodríguez Suárez; Farah María Kindelán Merceròn; Jorge Luis Pérez León; Monserrat Vázquez Sánchez; Mercedes Maturell Comas (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The COVID-19 is an emergent disease that has affected everybody in a pandemic way, with high sanitary, economic and social costs.   Objective: To characterize foreign patients confirmed with the COVID-19 in Santiago de Cuba, according to selected clinical epidemiological variables.   Methods: An observational, descriptive and cross-sectional study of 42 foreign patients who visited Santiago de Cuba province and tested positive to the COVID-19, who were referred to the health centers dedicated for their care was carried out from March to December, 2020. Some variables were analyzed, such as age, sex, residence municipality, origin country, months of more number of foreigners that visited the province and clinical course.   Results: The age group of more frequency was that of 30 - 44 years (14 patients for 33.3 %), followed by those affected of 45 - 59 years (11 for 26.2 %). The municipality of Santiago de Cuba had the higher risk of incidence (27 for 64.3 %). The most common clinical sign was the diffuse discomfort and the origin country that prevailed, United States (47.6 %). All the patients were imported.   Conclusions: The members of the case material had a favorable clinical course, that allowed to work, from the primary health care, in order to prevent the disease and to carry out the source of infection control as main tool to stop the transmission chain.